A COMPARATIVE STUDY BETWEEN THE CUSTOMARY INHERITANCE LEGAL SYSTEM OF THE COMMUNITY AND THE ISLAMIC INHERITANCE LEGAL SYSTEM ON INHERITANCE DISTRIBUTION IN MUKOMUKO CITY DISTRICT OF MUKOMUKO REGENCY - Vidyadhara Prawiratama Nugraha; Andry Harijanto; Akhmad Muslih (Universitas Bengkulu, 2023)
The writing of this research aims to: (1) understand and explain the inheritance distribution system according to the customary inheritance law of the Mukomuko community; (2) understand and explain the inheritance distribution system according to the Islamic inheritance law; (3) understand, study, and compare between the customary inheritance system of the community and the Islamic inheritance legal system on the inheritance distribution. This research used a normative research method with a comparative approach. A comparative approach is an approach to investigate the similarities and differences in things, people, work procedures, ideas, and critics towards other people, groups, and people’s perspectives on a group, a country, or an event. This research revealed that: (1) the inheritance distribution system according to the clan customary inheritance law, either high heirloom property (known as Harta Pusaka Tinggi) or matrimonial property, is subjected to matrilineal principles (the inheritance right of daughters are greater than the sons); (2) the inheritance distribution system according to the Islamic inheritance system is subjected to Qur’an with patrilineal principles (the inheritance right of sons are greater than the daughters); (3) the comparison of inheritance distribution according to the customary legal system of the community and the Islamic inheritance legal system have some similarities and differences. Both systems have tangent points in which the customary law of the community is individual-collective which is under the matrilineal principles while the Islamic inheritance law is individual-bilateral which is under the patrilineal principles. Keywords: A comparative study, the customary inheritance law of the community, the Islamic inheritance law.